Energy Crisis in Europe: The European Union’s Objectives and Countries’ Policy Trends—New Transition Paths? - Eva M. Urbano; Konstantinos Kampouropoulos; Luis Romeral (Energies, 2023)
Amidst the ongoing European energy crisis, the EU has proposed a legislative package to enhance gas independence from Russia, diversify energy supplies, and increase renewable energy targets. However, the urgency for energy security has led some countries to prioritise gas independence over decarbonisation, potentially sacrificing or delaying EU targets. Considering this framework, this article contributes to the body of knowledge by examining the electricity mix of the six most significant EU countries in terms of generation capacity, considers their alignment with 2025 energy transition goals, and analyses the latest legislative trends to evaluate their compatibility with EU objectives. The findings from these analyses indicate that EU members are currently prioritising gas independence, which has led to re-starting or extending the lifespan of coal-fired power plants and an increasing interest in nuclear energy as a low-carbon alternative. These findings have significant implications as they reveal how countries are being steered away from their pre-crisis energy transition paths, resulting in the formation of new perspectives for both the short and long term.